Virtual business center subsystem / Tham Wen Haur - Tham, Wen Haur (2003)
This report covers the overall specification development of Virtual Business center subsystem. The main objective of this project i to develop e-commerce website that can cater for the online purchase-selling processes specifically for student. With this system we introduce a unique feature of the system- Prepaid Token System. The first chapter of this report is to explain briefly an introduction to the whole system - E-Market. It covers overview of the project, problem specification, its objectives, project scope, expected outcome and project schedule . Chapter two will cover the literature review. This part discusses the topic like case study on the existing system on the internet, the definition of the e-commercer term, the workflow technology, scripting technology, hardware and software study and security issue had been looked at chapter four focused on the system analysis and the requirements identified based on the problem specification defined earlier. The last chapter here will cover the system architecture design, database design, flow chart and interface design. The language that i am using in this system in ENGLISH. English is a language that will become more and more common around the world. This system is target to the local university should incorporate with this advance system to let their students share this advance feature.